2021
DOI: 10.22365/jpsych.2021.043
|View full text |Cite
|
Sign up to set email alerts
|

Modern bioethical issues: Euthanasia, physician assisted suicide and abortion. Comparative study of attitudes between physicians and law professionals

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published during the production process, errors, may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…In 2000, a survey showed that four in five GPs considered themselves broadly pro-choice 17 and in an investigation into the attitudes of medical students in Britain, 73% of medical students did so 16 . Strong associations between attitudes towards abortion and the importance of religion are also seen in other studies 22,16,23,24 . We found no other research which compared attitudes towards abortion by service type or profession.…”
Section: Discussionsupporting
confidence: 80%
“…In 2000, a survey showed that four in five GPs considered themselves broadly pro-choice 17 and in an investigation into the attitudes of medical students in Britain, 73% of medical students did so 16 . Strong associations between attitudes towards abortion and the importance of religion are also seen in other studies 22,16,23,24 . We found no other research which compared attitudes towards abortion by service type or profession.…”
Section: Discussionsupporting
confidence: 80%
“…The metaphor of the "slippery slope" has been formulated in order to describe the expansion of the conditions of eligibility to E/PAS, which led to the admission of cases initially excluded through legislative regulations [69,70], as in the case of Canada. However, the metaphor can also be applied when referring to daily practice, where more and more requests for E/PAS can be considered valid; this is a risk defined by some authors as the "normalization" of E/PAS [71].…”
Section: The Slippery Slopementioning
confidence: 99%